Detection of hospital environmental contamination during SARS-CoV-2 Omicron predominance using a highly sensitive air sampling device - Tan, Kai Sen; Ang, Alicia Xin Yu; Tay, Douglas Jie Wen; Somani, Jyoti; Ng, Alexander Jet Yue; Peng, Li Lee; Chu, Justin Jang Hann; Tambyah, Paul Anantharajah; Allen, David Michael (Frontiers in Public Health, 2023)
Background and objectives The high transmissibility of SARS-CoV-2 has exposed weaknesses in our infection control and detection measures, particularly in healthcare settings. Aerial sampling has evolved from passive impact filters to active sampling using negative pressure to expose culture substrate for virus detection. We evaluated the effectiveness of an active air sampling device as a potential surveillance system in detecting hospital pathogens, for augmenting containment measures to prevent nosocomial transmission, using SARS-CoV-2 as a surrogate. Methods We conducted air sampling in a hospital environment using the AerosolSenseTM air sampling device and compared it with surface swabs for their capacity to detect SARS-CoV-2. Results When combined with RT-qPCR detection, we found the device provided consistent SARS-CoV-2 detection, compared to surface sampling, in as little as 2 h of sampling time. The device also showed that it can identify minute quantities of SARS-CoV-2 in designated “clean areas” and through a N95 mask, indicating good surveillance capacity and sensitivity of the device in hospital settings. Conclusion Active air sampling was shown to be a sensitive surveillance system in healthcare settings. Findings from this study can also be applied in an organism agnostic manner for surveillance in the hospital, improving our ability to contain and prevent nosocomial outbreaks.